Steroids for preventing recurrence of acute severe migraine headaches: a meta‐analysis. Issue 8 (11th April 2013) - Huang, Y.; Cai, X.; Song, X.; Tang, H.; Huang, Y.; Xie, S.; Hu, Y.
<x xml:space="preserve">Abstract</x> Background and purpose Recurrence of migraine headaches after treatment is common. The evidence regarding steroids for preventing migraine headache recurrence is controversial. This meta‐analysis examined the effectiveness of steroids for prevention of recurrent headaches. Methods Databases (PubMed, Embase and the Cochrane Library) and conference proceedings were searched for randomized controlled trials comparing steroids and placebo in the treatment of migraine headaches. Two independent reviewers assessed studies and extracted data. Relative risks (RRs) of headache recurrence and adverse events were calculated and reported with 95% confidence intervals (95% CIs). Results Eight studies with 905 patients were included. Pooled analysis showed that when steroids were added to standard abortive therapy they reduced the rate of moderate or severe headache recurrence after 24–72 h of follow‐up evaluation (RR = 0.71; 95% CI = 0.59–0.86). There was no significant benefit of steroids compared with placebo in the proportion of totally resolved migraines (RR = 1.11; 95% CI = 0.94–1.32). The side effects of steroids are mild and not significant except for dizziness. Subgroup meta‐analysis showed that parenteral dexamethasone tends to be more effective in reducing moderate or severe recurrent headaches (RR = 0.68; 95% CI = 0.55–0.84). However, no significant differences were found between oral administration and parenteral administration of steroids (P = 0.37). Conclusion When steroids are added to standard abortive therapy for migraine headaches, they are effective and safe for preventing moderate or severe headache recurrence.